Kawasaki Disease in the neonate: case report and literature review - Fajer Altammar; Bianca Lang (BMC, 2018)
Abstract Background Kawasaki Disease (KD), the leading cause of acquired heart disease in children in the developed world, is extremely rare in neonates. We present a case of incomplete KD in a neonate and a review of the literature on neonatal KD. Case presentation A previously healthy full term 15 day old Caucasian male with an unremarkable antenatal and perinatal history, presented on Day 2 of illness with fever, rash, irritability, and poor feeding. Examination revealed fever (39.6C), tachycardia, tachypnea, extreme irritability, and a generalized maculopapular rash, but was otherwise normal. His complete blood count, CRP and ESR were normal. Empiric intravenous antibiotics and acyclovir resulted in no improvement. On day 4, he had ongoing fever and developed recurrent apnea, required supplemental oxygen, and was transferred to the pediatric intensive care unit. On day 6, he developed bilateral non-purulent conjunctivitis, palmar erythema, bilateral non-pitting edema and erythema of his feet, and arthritis. His full septic work-up and viral studies were negative. On Day 7 he was treated with intravenous immunoglobulin, and over the next 48 h his symptoms including extremity edema resolved, he no longer required supplemental oxygen, and fever did not recur. On day 9 of illness he had marked thrombocytosis. Subsequently, he developed distal extremity desquamation. Repeated echocardiograms excluded the presence of coronary artery aneurysms (CAA). Conclusions We believe this to be a rare case of incomplete KD in a neonate, in which timely IVIG administration led to resolution of the acute illness and may have prevented CAA. A comprehensive English-language medical literature review of KD presenting in the neonatal period revealed only fifteen case reports. Cases often presented with incomplete KD, and a number had atypical laboratory features including a normal CRP in the acute phase, similar to what was seen in our patient. This case and our literature review should increase awareness that KD can rarely occur in neonates, often presenting atypically. Recognizing KD in a neonate enables appropriate treatment that can result in resolution of symptoms and may decrease the risk of cardiac complications.